A Systematic Analysis: Website Development using Codeigniter and Laravel Framework - Onno Widodo Purbo (Enrichment : Journal of Management, 2021)
The use of the website as one of the most influential means of communication in various human activities has been so widespread with a low cost factor, the website is often functioned as a medium for storing data and information using certain topics, besides that the website is also a collection of web pages that related to each other on the web. In general, there are several programming languages that are used to create website applications. such as, HTML (Hyper Text Markup Language), PHP (PHP Hypertext Preprocessor), CSS (Cascading Style Sheet), Javascript, Mysql, and jquery. The CodeIgniter is an open or open source application based on the PHP framework with the MVC model or also commonly called the Model View Controller which is used to build a dynamic website using PHP code. CodeIgniter helps make it easier for developers or developers to be able to create a website-based application very quickly and quickly. In this study, analysis and comparison of the accuracy of preventing SQL injection attacks is carried out on the CodeIgniter framework and the Laravel framework. In the CodeIgniter framework, the escaping query function is used to prevent SQL injection attacks. Meanwhile, the Laravel framework uses the loquent ORM function to prevent SQL injection attacks. The Codeigniter and Laravel frameworks have different time and speed performance results. Codeigniter has a higher average time and speed than Laravel. In the average time value, Codeigniter has a greater time duration than Laravel with a difference of 4.2 ms and in the average speed value, Codeigniter is still superior with a difference of 40.08 Kbit/s from Laravel.